The Study of Egg Allergy in Children With Atopic Dermatitis - Tahmineh Salehi, MD; Zahra Pourpak, MD, PhD; Shahnaz Karkon, MD; Raheleh Shokouhi Shoormasti, MSc; Samineh Kamali Sabzevari, MSc; Masoud Movahedi, MD; Mohammad Gharagozlou, MD; Mostafa Moin, MD (World Allergy Organization Journal, 2009)
Context: Food allergy plays a significant pathogenic role among children with atopic dermatitis (AD).Objective: The aims of this study were to evaluate allergy to egg in these children and determine the egg specific immunoglobulin E (IgE) cutoff point.Design and Setting: It was a cross-sectional study that took place at Immunology, Asthma and Allergy Research Institute from 2005 to 2007.Methods: Children younger than 14 years old with AD entered the study. Careful medical histories were taken and skin prick and Immuno-CAP tests with the most commonly offending foods (cow's milk, egg, wheat, peanut, and soy) were performed. Children with a clear, positive history of food allergy and a positive IgE-mediated test or those with positive responses to both IgE-mediated tests were determined to have food allergies. The egg-specific IgE level cutoff point was determined.Results: A hundred patients entered the study (from 2 months to 12 years old). They were divided into 3 age groups: first <2 years, second from 2 to <6 years, and third from 6 to 14 years. The most common food allergens were egg (39.22%) in the first, cow's milk (35.13%) and egg (32.43%) in the second, and peanut (25%) and egg (16.67%) in the third group. The egg-specific IgE cutoff point value was 0.62 kUA/L (kilounits of allergen-specific IgE per liter). The positive predictive value was 95%.Conclusion: Prevalence of egg allergy is highly significant in patients with AD.To use egg-specific IgE level cutoff point, the patient population under study must be considered. Keywords: egg allergy, atopic dermatitis, food allergy, specific IgE cutoff point